Perbaikan manajemen pakan dan pengolahan susu kambing PE di kelompok Peternak Muda Mandiri di Kabupaten Indragiri Hulu Riau - Evy Rossi; Fajar Restuhadi; Akhmad Ibrahim R. S. Hasibuan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The objectives of community service were to) improve the ability of Etawah breed goat breeders (PE) in feed management and milking and b) increase the ability of farmers to innovate in developing the diversification of fresh milk into functional food. The method of implementation was carried out by extension and demonstration plots on feed management by utilizing palm leaves to be used as a complete feed ingredient formulated using other feed ingredients such as agricultural waste or other agricultural industries.Based on observations during the demonstration plot it was compared with PE goats that were kept semi-intensively on the average level of ration consumption and body weight gain per day. The average body weight gain of PE goats receiving a complete ration in the form of pellets (615.50 g / head / day) is higher than the consumption rate of livestock (566.50 g / head / day) which were kept by breeders semi-intensively. The body weight gain of the demonstration plot cattle was 193.50 g/head/ day which was higher than the body weight gain of PE goats kept by breeders (54.90 g/head/day). The introduction and practice of processing milk into functional food had been carried out by processing milk into fermented drinks in the form of yogurt and kefir and their derivative products. From this activity, it can be concluded that by improving feed management and meeting the needs of livestock, milk production can increase. The improvement of farmer science and technology had a positive impact on the orientation of raising PE goats not only for savings but also as a producer of milk which was economically very high in value.